Resistance of grassland productivity to hydroclimatic changes in the Tibetan Plateau - Na Zeng; Zhongen Niu; Pan Li; Xiaobo Zhu; Xiaoli Ren (Ecological Indicators, 2022)
An increasing trend of hydroclimatic disturbances, such as droughts, which are projected to become more frequent and intense with global warming and climate change. Droughts adversely affect the structure and function of terrestrial ecosystems, damage vegetation growth, and even increase mortality. In this study, we assess the drought resistance (Rd) of ecosystems in the Tibetan Plateau. Ecosystem water use efficiency (WUE) was used as an indicator of change in carbon and water cycles, and then ecosystem resistance in terms of change in WUE in drought years was analyzed. Our results suggested that the WUE in the Tibetan Plateau exhibited significant spatial heterogeneity and drastically reduced under dry and cool conditions. The evaluation of ecosystem drought resistance indicated that the grassland in most areas of the Tibetan Plateau is resistant to hydroclimatic fluctuations. In particular, the grassland ecosystem in areas with lower temperatures or higher precipitation exhibited greater drought resistance. Our results facilitate the identification of drought-vulnerable areas in the Tibetan Plateau to inform grassland ecosystem management and climate policy-making and sustain ecosystem stability under future climate conditions.